2017
DOI: 10.1021/acsami.6b16050
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolyzable Nanoparticle Tracers for Environmental Interrogation and Monitoring

Abstract: Environmental tracing applications require materials that can be detected in complex fluids composed of multiple phases and contaminants. Moreover, large libraries of tracers are necessary in order to mitigate memory effects and to deploy multiple tracers simultaneously in complex oil fields. Herein, we disclose a novel approach based on the thermal decomposition of polymeric nanoparticles comprised of styrenic and methacrylic monomers. Polymeric nanoparticles derived from these monomers cleanly decompose into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The accuracy and resolution of the depth at which cuttings are collected varies based the drill bit, rate of drilling, and lag time varying for different particle sizes but is typically around 10 ft. Multiple studies have been undertaken to improve the accuracy by modeling the lag distribution of the particle or the use of depth tags. , In conventional reservoirs, some work has already been performed to use drill cuttings as a form of mud logging. These techniques have covered a wide range of measurement techniques, including optical microscopy, computed tomography (CT), γ-ray, X-ray diffraction (XRD), X-ray fluorescence (XRF), porosimetry, NMR, or a combination of these .…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy and resolution of the depth at which cuttings are collected varies based the drill bit, rate of drilling, and lag time varying for different particle sizes but is typically around 10 ft. Multiple studies have been undertaken to improve the accuracy by modeling the lag distribution of the particle or the use of depth tags. , In conventional reservoirs, some work has already been performed to use drill cuttings as a form of mud logging. These techniques have covered a wide range of measurement techniques, including optical microscopy, computed tomography (CT), γ-ray, X-ray diffraction (XRD), X-ray fluorescence (XRF), porosimetry, NMR, or a combination of these .…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR-ATR spectra were collected at a 4 cm −1 resolution over a 4000−600 cm −1 range. 1 H and 13 C NMR data were collected on a Bruker AVANCE III 500 MHz NMR instrument. The NPs were dissolved in 1 mL of deuterated tetrahydrofuran (THF-d 8 ), and the NMR spectra were collected at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…We have proposed to use barcoded polymeric nanoparticles (NPs) as tags to label the drill cuttings when they are generated at the drill bits 13,14 and have demonstrated that labsynthesized polystyrenic NPs display clean and predictable depolymerization patterns that can be detected using pyrolysisgas chromatography−mass spectrometry (Py-GCMS). 13 However, in the practical oil field applications, matrix interferences present significant challenges in unambiguous detection of the polymeric NPs recovered from downhole, especially at subnanogram levels. During the trip downhole, NPs are buried in a very viscous and complex mixture of sand, carbonates, clays, fluids, and additives such as polysaccharides, 15 polyacrylamides, polyamides, chain surfactants, biocides, and scale inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal systems of functionalized nanoparticles have been evaluated in oil industry for enhanced oil recovery, formation damage remediation, flow assurance, and water treatment operations [1]- [8]. Surface modified nanoparticles have also been considered for applications as tracers in reservoir studies, active media in thermal management fluids, and fillers in high performance elastomers [9] [10] [11] [12] [13]. Conventional functionalization of nanoparticles, which mostly use alkoxysilanes and chlorosilanes for covalent bonding to surface, need catalytic amount of water for the reactions to proceed, require multiple hours to fully saturate the surface, and release by-products capable of interfering with the desired functional or chemical behavior of the modified surface [14].…”
Section: Introductionmentioning
confidence: 99%